A Bibliometric Analysis of the Occupational Therapy Literature Addressing Interventions for Children and Adolescents with Mental Health Needs. (2nd January 2022) - Gutman, Sharon A.; Brown, Ted; Precin, Pat; Chan, Lauren J.; Czuj, Devin C.; Hartman, Brooke N.; Meindl, Brittany M.; O'Connor, Amanda R.; Safrin, Atara; Stein, Jennifer N.; Wolinsky, Julia H.
Abstract: A bibliometric analysis was performed to examine the occupational therapy peer-reviewed literature addressing interventions for children and adolescents with mental health disorders (1980–2019). The search strategy yielded 82 articles that have not produced significant support for the profession's role in this practice area, have not been well-cited, and may not be readily accessible by stakeholders. A third of this literature addressed children with ADHD using sensory-based approaches. Depression, anxiety, and bipolar disorder were addressed comparatively less. The profession must increase advocacy to enhance awareness of therapists' role in this practice area and engage in research supporting practice.